2019
DOI: 10.4314/wsa.v45i2.09
|View full text |Cite
|
Sign up to set email alerts
|

Leachate seepage from landfill: a source of groundwater mercury contamination in South Africa

Abstract: Mercury has been used for many centuries in the production of consumer products such as thermometers, electrical switches, fluorescent light bulbs, batteries, biocides and pesticides, cosmetics and dental amalgam filling, among others. After use, these mercury-containing consumer products form part of the municipal solid waste (MSW). As a result of an unseparated solid waste collection system, mercury-containing wastes tend to end up in landfills where mercury and other pollutants can leach out of products int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The pH effect was investigated; 100 mg • dm -3 of tetracycline solutions were prepared in the pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). After adjustment, the solutions were mixed with 0.3 g of adsorbent during 24 h at 298 K. The pH was adjusted by using 0.1 N of HCl or KOH according to the desired pH value.…”
Section: Ph Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH effect was investigated; 100 mg • dm -3 of tetracycline solutions were prepared in the pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). After adjustment, the solutions were mixed with 0.3 g of adsorbent during 24 h at 298 K. The pH was adjusted by using 0.1 N of HCl or KOH according to the desired pH value.…”
Section: Ph Effectmentioning
confidence: 99%
“…Therefore, the composition of leachates is very difficult to determine. Despite the complexity of the effluent, it is 1 Scientific and Technical Research Center in Physico-Chemical Analysis, PO box 384, Headquarters ex-Pasna Industrial area Bou-Ismail, zip code 42004 Tipaza, Algeria, phone +213(0)24325774, fax +213(0)24325774, ORCID: 0000-0002-1432-7237 2 LPCEMAE Laboratory, Faculty of Chemistry, Houari Boumediene University of Science and Technology (USTHB), PO box 32 ELALIA, Bab Ezzouar Algiers, Algeria, email: bhamdi_99@yahoo.fr, ORCID: 0000-0002-5502-1605 3 Controlled Porosity Materials Team, Institute of Materials Sciences of Mulhouse UMRCNRS 7361, University of Strasbourg, University of Haute Alsace, ENSCMu, 3 rue Alfred Werner, 68093 Mulhouse Cedex, France, email: jocelyne.brendle@uha.fr, ORCID: 0000-0001-5266-6224 possible to identify these xenobiotic compounds [9][10][11][12][13][14][15][16]: phenols, chlorinated aliphatic compounds, aromatic hydrocarbons, tetracycline, pesticides, and plasticizers.…”
Section: Introductionmentioning
confidence: 99%
“…This landfill lacks a leachate collection system, and thus frequent groundwater pollution is recorded [106]. This is similar to the Granville Brooke and Garankuwa landfills in Sierra Leone and South Africa, respectively [101,107].…”
Section: Landfill Operationsmentioning
confidence: 90%
“…In the study by Panichev et al (2019), five provinces of South Africa were sampled between 2013 and 2017; and the lichens analysed to provide time-integrated data, which correspond to the mean Hg concentration in air at a specific location over a long time period. Nevondo et al (2019) suggested that Hg coming from contaminated groundwater from landfill leachate seepage could carry significant amounts of Hg, especially in landfills that are not lined with a geomembrane. Bieser et al (2020) investigated sources and sinks of Hg at Cape Point, South Africa by combining atmospheric Hg data with a trajectory model; and found that continent is the major sink, and the ocean, especially its warm regions (i.e., the Agulhas Current), is the major source for Hg.…”
Section: Analytical Determinationmentioning
confidence: 99%